COMMUNITY-BASED ACTIVITY OF NURSERY RAISING FOR IMPROVING THE LIVELIHOOD OF SMALL SCALE’ FARMER in District Kurram - Farhan Ahmad; Iftikhar Khan; Muhammad Nasib; Ali Sher (Jurnal Hexagro, 2022)
Income generation through community-based Nursery raising technique, Nursery raising, and maintenance in the area is a new Intervention being carried out in the villages of Kurram. In selected villages, poor and deserving farmers were selected to execute the activity to improve the livelihoods of the deserving and needy beneficiaries selected in the Broad-Based Community Meeting (BBCM) for Nursery Raising activity. A total of 124 beneficiaries in Kirman Mamuzai, Kirman Mata, Shakh, and Shaikh Dawlat Khel villages were identified for 24 different nurseries as simple randomized sampling. The data were analyzed descriptively in a one-sample t-test in different training sessions to manage the nurseries accordingly. The result showed that nurseries activity could be sustained for developing entrepreneurship. There has been an increasing demand for fruit plants plantation more. Nursery product is no longer restricted to large parks and gardens. It has entered into a high rise. Walnut, Pomegranate, Peach and Apricot plantation, etcetera. Heavy demand is observed during the assessment phase of the project. Whether local or introduced species, Nursery Seedlings have better survival than seeds sown directly in the Kurram district. So, nursery seedling becomes the planting material for plantations is a high source of Income.